2021
DOI: 10.1021/acs.oprd.1c00031
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Synthesis of Delgocitinib, a JAK Inhibitor for the Treatment of Atopic Dermatitis

Abstract: Herein is reported the nine-step commercial synthesis of delgocitinib, a Janus kinase inhibitor approved for the treatment of atopic dermatitis in 2020. Its chiral spirodiamine core was selectively constructed by an intramolecular SN2 reaction of the suitably designed γ-lactone substrate and a few subsequent steps including a selective γ-lactone ring-opening reaction with potassium phthalimide, hydrazine-free mild dephthaloylation, and one-pot reduction of β- and γ-lactams. The route affords chemically and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Delgocitinib contains a stereochemically complex spirocyclic diamine subunit spanning a pyrrolopyrimidine ring system and a cyanoacetic amide, structurally resemblant to several other previously approved JAK inhibitors including tofacitinib. A stereocontrolled kilogram scale synthesis of delgocitinib has been disclosed, beginning with an S N 2 reaction involving bromolactone 128 and benzyl amine to provide α-amino lactone 129 (Scheme ), which was isolated as the HCl salt after precipitation from hydrochloric acid in ethyl acetate . Amine 129 was then acylated with enantiomerically pure acid chloride 131 (prepared by thionyl chloride treatment of commercial acid 130 ) to furnish lactone 132 .…”
Section: Inflammation/immunologic Drugsmentioning
confidence: 99%
“…Delgocitinib contains a stereochemically complex spirocyclic diamine subunit spanning a pyrrolopyrimidine ring system and a cyanoacetic amide, structurally resemblant to several other previously approved JAK inhibitors including tofacitinib. A stereocontrolled kilogram scale synthesis of delgocitinib has been disclosed, beginning with an S N 2 reaction involving bromolactone 128 and benzyl amine to provide α-amino lactone 129 (Scheme ), which was isolated as the HCl salt after precipitation from hydrochloric acid in ethyl acetate . Amine 129 was then acylated with enantiomerically pure acid chloride 131 (prepared by thionyl chloride treatment of commercial acid 130 ) to furnish lactone 132 .…”
Section: Inflammation/immunologic Drugsmentioning
confidence: 99%
“…In addition, Takiguchi et al have also reported the stereocontrolled synthesis of delgocitinib [ 97 ]. The synthesis was started with 3-bromodihydrofuran-2(3 H )-one 46 , which was converted to 49 in a three-step synthesis, Scheme 6 .…”
Section: Introductionmentioning
confidence: 99%